Molecular Determination of Toxigenic Potential of Fusarium spp. Isolated from Seeds of Wheat (Triticum aestivum) Genotypes and Evaluation of Levels of Fumonisins in the Grains at Harvest in Three Major Wheat Producing Counties in Kenya - Phanice Kheseli Otieno; Susan S. Imbahale; Vitalis Wafula Wekesa; Miriam Otipa; Sheila Okoth (International Journal of Agronomy)
Infestation of cereals such as wheat by pathogenic Fusarium species (Fusarium spp.) is associated with over 25% weight loss of the grain and accumulation of hazardous mycotoxins. Potential management strategies against the pathogens include the development of more resistant wheat genotypes and the development of rapid and accurate Fusarium spp. identification methods, among other control measures. This study evaluated the toxigenic potential in populations of Fusarium spp. isolated from seeds of locally developed wheat genotypes and levels of fumonisins in the grains at harvest in three counties in Kenya. The sampling of the wheat grains took place between September 2016 and October 2017. Determination of toxigenic potential was PCR based using Tri13F/Tri13DONR and FUM1F/FUM1R specific primer pairs while detection of fumonisin levels was done using Total Fumonisin Assay 0.25/5.0 ELISA kit. Data were analyzed using ANOVA and the Tukey HSD test. FUM1 gene was detected in 60% of the Fusarium spp. analyzed. The distribution of the gene within the isolates across the three regions was as follows: Narok: 54%, Uasin Gishu: 25%, and Nakuru: 21%. Tri13DON gene was not detected in the assessed potential deoxynivalenol (DON) producers. Fumonisin levels in the wheat samples from the three counties were significantly different (p<0.001). The highest fumonisin levels, 9.6 ppm, occurred in 30.7% of the grains of the studied wheat genotypes. Relatively high fumonisin levels occurred in Njoro II, Eagle 10, Robin, and Korongo wheat genotypes with no significant difference at 0.05 confidence interval. In conclusion, the toxigenic potential amongst the Fusarium spp. studied was confirmed based on the occurrence of FUM1 gene and the detection of fumonisins in 76% of the sampled wheat grains. More research is recommended to ascertain the prevalence of the genes determining the production of DON and the other trichothecenes in Fusarium spp. prevalent in the developed wheat genotypes in the different agroecological regions in Kenya. In addition, the assessment of the occurrence and levels of the respectful mycotoxins also needs further research. These would provide additional information for the improvement of strategies put in place to manage the effects of the pathogenic Fusarium spp. in the crop and to ensure mycotoxin safety of the wheat food chain for both livestock and human consumption. It also shows the need for the development of more disease-resistant wheat varieties by wheat seed-producing companies.